Logistics - Korucuk, Selçuk; AYTEKİN, Ahmet (Journal of process management and new technologies, 2024)
Logistics companies are increasingly focusing more on technological transformation and development to save costs and transition to a more flexible structure, and their business objectives are closely tied with this framework. Changing business processes and technological revolutions force logistics companies to become more adaptive and agile, demanding the creation of organizational procedures in this context. To do this, the technology revolution, also known as logistics 4.0, is gaining popularity in the logistics industry and playing an essential role in cost savings for businesses. Logistics 4.0 applications are one approach for implementing procedures in logistics organizations in an effective and efficient manner. However, logistics 4.0 applications encounter many administrative and operational barriers. In this regard, the study identified and weighted barriers to logistics 4.0 applications in logistics companies with corporate identities. The polytopic fuzzy RANCOM approach was employed for this aim. The study found that "costs of implementing logistics 4.0" and "necessity of implementing process-driven management approaches" are the most significant barriers to implementing logistics 4.0, while "existence of cyber-attack threats" is the least important criterion.